STUDENTS' ABILITY IN USING INDEPENDENT AND DEPENDENT CLAUSES IN COMPLEX SENTENCES AT SIXTH SEMESTER STUDENTS OF UNIVERSITAS BOSOWA - Bustang, Bustang (Fakultas Keguruan dan Ilmu Pendidikan, 2017)
The research is aimed to know the students’ ability in using Independent and Dependent Clauses in Complex Sentences in class VI-A and VI-B at Bosowa University. The result of this research is expected to give benefits for the readers especially in using Independent and Dependent Clauses in Complex Sentences. This research used descriptive qualitative research. The populaton of this research is sixth semester students of Bosowa University in academic year 2015/2016 that have 65 students and the sampling of this research is quota sampling so, in this research the researcher take some of the students in the class which is consist of 30 students  from two classes and each class was took 15 students. The result of this research and explanation that the researcher got in Bosowa University is 6.6% students got very good category and 20% students got good category while 50% students got enough category and then 23.3 students got poor category. While the mean score of the students is 71.2. It indicates that students sixth semester enough ability in using Independent and dependent clauses in complex sentences.